Análise de estimulantes em suplementos alimentares e produtos naturais a base de plantas comercializados para fins de emagrecimento no Brasil - Zemolin, Gabriela Mezzomo (2015)
The strong advertising appeal, the search for a good physique, and the improvement in physical performance, has risen the popularity of food supplements and other therapies with slimming supplements based on plant extracts. Since the law exempts food supplements from registration, they are easy targets for importation, commercialization e consumption by the population, which worsens malpractice cases of adulterations. Thus, the objectives of the present work were: research the presence of stimulants in food supplements for both slimming and weight gain; study the addition of synthetic caffeine in natural products based on plants used for weight loss; develop chromatographic methods using HPLC with photodiode detection to detect caffeine, salicin, ephedrine, hordenine, tyramine, octopamine and synephrine (including the L and D enantiomers). The stimulants were separated by reverse phase chromatography using octadecylsilane columns (C18). For L and D synephrine, chromatography with chiral phase of β-cyclodextrin was used. Detection limits varied from 0.02 mg L-1 to 0.35 mg L-1, while quantification limits ranged from 0.07 mg L-1 to 1.16 mg L-1 for the separation of stimulants in food supplements. For analyses of caffeine in herbal products, the LOD and LOQ were 0.048 mg L-1 and 0.16 mg L-1, respectively. For the anlysis of the enantiomers of p-synephrine, the L enantiomer presented a detection limit of 0.11 mg L-1 and quantification limit of 0.36 mg L-1, while the D enantiomer exhibited a detection limit of 0.41 mg L-1 and a quantification limit of 1.36 mg L-1. Each method developed was then applied to the sample, which were, dietary supplement samples (n = 47), herbal products (n = 100), and fruits of Citrus aurantium. Caffeine was the most frequent of the studied stimulants, often exceeding the labeled content and the maximum dose per day recommended (420 mg). The food supplements presented caffeine, synephrine and ephedrine as main stimulants in 53% of the studied samples.